(untitled) (Research, Society and Development, 2020)
A technologocal tool is used to measure the effectiveness of students’ learning in the subjects os Statistics I adn Statistics II of the Administration course, ande in the Statistic subjects of the Production Engeneering and Accounting Sciences courses of a university center in Zona dmore interesa Mata Mineira; this tool has proven to be useful and agile for real feedback on class learning. The tool in study is called Plickers, being classified as Classroom Response. In mentioned subjects, the tool was integrated into the classes using the Peer Instruction Methodology (PI), in which students learn frim their peers. The tool was well accepted by students who were instantly more interested in classes and new technology, as shown by the results. The fact that each studant has a presponse card, for exclusive use, makes the students’ omission, when answering a question proposed by the teacher, non-existent. This way, this is no longer a problem in the classroom, the teacher has, quickly, the real leaning diagnosis of his students, this allows measures to be taken, when learning can be considered unsatisfactory. The tool allows dynamism during classes, allowing the teacher to make decisions and paths that can revesse unsatisfactory situations.